The Potential of Clinical Decision Support Systems for Prevention, Diagnosis, and Monitoring of Allergic Diseases - Dramburg, Stephanie; Marchante Fernández, María; Potapova, Ekaterina; Matricardi, Paolo Maria (Frontiers in Immunology, 2020)
Clinical decision support systems (CDSS) reinforce health care professionals (HCP) in taking informed decisions during their clinical routine. CDSS are becoming particularly important in the perspective of precision medicine, when health care professionals need to consider growing sets of information to create precise patient profiles for personalized diagnosis, treatment and outcome monitoring. In allergy care, several CDSS are being developed and investigated, mainly for respiratory allergic diseases. Although the proposed solutions address different stakeholders, the majority aims at facilitating evidence-based and shared decision-making based on guidelines, and real-time clinical data. We offer here an overview on existing tools, new developments and novel concepts and discuss the potential of digital CDSS in improving prevention, diagnosis and monitoring of allergic diseases.